A FRESH Take on Resolution in 3D Bioprinting. Issue 11 (November 2019) - Corbett, Daniel C.; Olszewski, Emily; Stevens, Kelly
Abstract : Recent innovations in the materials used for bioprinting have enabled transformative gains in the resolution and architecture of 3D-printed engineered tissues. We focus here on one of these innovations, reported byLee et al., which lowers the resolution limit for printing soft biomaterials.